1990
DOI: 10.3382/ps.0691702
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Dietary Level of 1α,25-Dihydroxycholecalciferol for Eggshell Quality in Laying Hens

Abstract: The optimal dietary level of 1 alpha,25-dihydroxycholecalciferol [1,25-(OH)2D3] for eggshell quality was established. White Leghorn hens, 59 wk of age, were fed one of eight diets that contained the same basal ingredients, including 3.1% calcium, but different levels (microgram/kg) or forms of calciferol supplements: no calciferol supplement of any form (56 hens); 27.5 (control) or 55.0 micrograms of cholecalciferol (56 hens each); 3, 5, or 7 micrograms of 1,25-(OH)2D3 (28 hens each); 5 micrograms of 24,25-dih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Present study has shown a good response in FCR in layers fed C. diurnum leaf powder. Tsang et al [16] also observed that feed consumption progressively decreased with increased dietary 1,25(OH) 2 D 3 . Probably, C. diurnum leaf which contain enough 1,25(OH) 2 D 3 levels must have resulted in lesser consumption of feed.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Present study has shown a good response in FCR in layers fed C. diurnum leaf powder. Tsang et al [16] also observed that feed consumption progressively decreased with increased dietary 1,25(OH) 2 D 3 . Probably, C. diurnum leaf which contain enough 1,25(OH) 2 D 3 levels must have resulted in lesser consumption of feed.…”
Section: Discussionmentioning
confidence: 93%
“…If we compute the additional eggs gained by preventing the drop due to the inclusion of C. diurnum leaf powder in the layer feed would result in extra eggs of about 25 per bird for the entire egg laying period of a hen. Tsang et al [16] demonstrated that decreased egg production is related to the ageing process in the layers. Though present study also on par with literature with respect to the age but the egg production drop was prevented to a larger extent up to 72 weeks in C. diurnum leaf powder fed layers suggests that 1,25(OH) 2 D 3 maintains the egg production at higher levels.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Tsang et al (1990b) have shown further that the optimal dietary level of calcitriol is 5 ug/kg, and that there is a very narrow margin between the optimal level and the toxic level (7 ug/kg). However, there have been few studies to test the direct effect of these metabolites on egg breakage.…”
Section: Introductionmentioning
confidence: 95%